Meiotic recombination and synapsis in wild-type and asynaptic mutants of tomato (Solanum lycopersicum) - Qiao, Huanyu, author; Anderson, Lorinda K., advisor; Stack, Stephen, committee member; Bedinger, Patricia A., committee member; Ranu, Rajinder Singh, committee member (Colorado State University. Libraries, 2010)
Recombination nodules (RNs) and synaptonemal complexes (SCs) are meiosis-specific structures that play important roles in crossing over. During pachytene, RNs mark crossover sites along SCs. MLH1, a mismatch repair protein, promotes crossing over and is a component of most RNs. In wild-type tomato, each bivalent has one, two or three crossovers (=chiasmata), and the number and distribution of these crossovers is affected by crossover interference (the tendency for one crossover to reduce the likelihood of another crossover nearby). Although the phenomenon of genetic interference was discovered nearly one hundred years ago, its molecular basis is still unknown. SCs occur between pairs of homologous chromosomes (bivalents) during prophase I and consist of two parallel rod-like lateral elements held together by transverse fibers. Each lateral element is associated with the two sister chromatids of one of the homologous chromosomes. Cohesin complexes consisting of four proteins (SMC1, SMC3, SYN1/REC8 and SCC3) are found in lateral elements and link sister chromatids together. My research addressed the question of how synapsis (SC formation) is related to the frequency and control of crossing over using tomato, particularly the as1 meiotic mutant, as a model system. Meiocytes from tomato plants homozygous for the mutation as1 do not complete chromosome synapsis and have few chiasmate bivalents, resulting in unbalanced chromosome segregation and sterility. We found a severe delay of prophase I in the as1 mutant compared to wild-type tomato using an in vivo BrdU labeling method, which may be related to the asynaptic phenotype. The asynapsis and delay in the as1 mutant are not likely to be due to a defect in the early steps of recombination, since the frequency and distribution of early recombination proteins (MRE11, RAD50, and RAD51) are similar in wild-type and in the as1 mutant. EM immunolabeling demonstrated that MLH1, a late recombination protein, is present in a subset of RNs in as1, an observation similar to that in wild-type. However, RNs in as1 are larger than those in wild-type. Previous work by other researchers showed a normal level of crossovers in several genetic intervals of the as1 mutant, which was unexpected based on the high degree of asynapsis observed at the cytological level. To evaluate crossing over in the as1 mutant, we examined the immunolabeling patterns of MLH1 foci that mark crossover sites. In as1 meiocytes, we observed that most MLH1 foci were associated with SC segments between two homologous chromosomes. We found that the number of MLH1 foci per micrometer is higher in the as1 mutant compared to wild-type. In addition, interference between MLH1 foci was lower in the mutant than in wild-type tomato. The weakened genetic interference in the as1 mutant may be due to a defect of the medium of interference, since early events of the recombination pathway in as1 seem normal, and MLH1 foci representing crossovers, the last step of the recombination pathway, are still present in the mutant. A good candidate to transmit interference is the cohesin complex that makes up a part of lateral elements. Compared to wild-type, we observed reduced immunofluorescence for the cohesins SMC1, SYN1, and SCC3, but not SMC3 in the as1 mutant. Although we do not yet know the specific mutation of as1 in tomato, we have shown that the asynaptic phenotype is accompanied by alterations in cohesin proteins in AE/LEs and in the distribution of MLH1 foci compared to wild-type. To our knowledge, this is the first report of an association between cohesin proteins and crossover interference regulation in any organism. This discovery represents a significant advance in our efforts to understand the molecular basis of crossover interference.
Keywords: synaptonemal complex; recombination nodule; recombination; cohesion; Meiosis; Tomatoes -- Breeding -- Genetics; Genetic recombination; Recombinant DNA; Crossing over (Genetics); Meiosis